2011
DOI: 10.1097/iae.0b013e3181eef0ae
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sildenafil Citrate on Choroidal Thickness as Determined by Enhanced Depth Imaging Optical Coherence Tomography

Abstract: Sildenafil citrate appears to increase choroidal thickness as measured by eye-tracked enhanced depth imaging spectral-domain optical coherence tomography measurements in healthy subjects 1 hour and 3 hours after ingestion. These findings may be of relevance given that increased choroidal thickness appears to be a risk factor for central serous chorioretinopathy and that several reports have suggested an association between phosphodiesterase-5 inhibitors and this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(95 citation statements)
references
References 23 publications
3
89
1
2
Order By: Relevance
“…16 In previous studies, sildenafil citrate has been reported to increase choroidal thickness due to a vasodilatory effect of sildenafil citrate on the choroidal circulation. 17 This correlation was further investigated by Kim et al 18 using swept-scan high-frequency digital ultrasound to measure the ocular blood flow. In addition, in a latter study by Ulas¸et al, 19 significant choroidal thinning was noted in chronic renal failure patients after hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…16 In previous studies, sildenafil citrate has been reported to increase choroidal thickness due to a vasodilatory effect of sildenafil citrate on the choroidal circulation. 17 This correlation was further investigated by Kim et al 18 using swept-scan high-frequency digital ultrasound to measure the ocular blood flow. In addition, in a latter study by Ulas¸et al, 19 significant choroidal thinning was noted in chronic renal failure patients after hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in two different studies, the authors reported that sildenafil citrate increases choroidal thickness because of the vasodilatory effect of sildenafil citrate on the choroidal circulation. 25,26 Histopathological studies showed that PEX accumulations in the ocular and peribulbar tissues have been detected not only in affected eyes, but also clinically unaffected eyes and therefore it was stated that the socalled unilateral PEX syndrome is clinically asymmetric rather than truly unilateral. 27 Our study showed that the eyes of patients in the bilateral PEX group (group 3) and the affected eyes of the patients in the unilateral PEX group displayed choroidal thicknesses that were thinner than those of the eyes of normal subjects (group 4) and the unaffected eyes of the patients in the unilateral PEX group (group 2).…”
Section: Discussionmentioning
confidence: 99%
“…We also excluded patients taking medication implicated in altering the choroidal vasculature, including corticosteroid and sildenafil. 20,21 For the estimation of SFCT, after complete resolution of SRF in CSC, SFCT of 32 normal volunteers were also evaluated.…”
Section: Methodsmentioning
confidence: 99%